Studi Fenomenologi: Pengalaman Mahasiswa Praktik Klinik Pendidikan Profesi Ners Pada Masa Pandemi Covid-19 - Sidaria, Sidaria; Murni, Dewi; Maisa, Esthika Ariany (Universitas Fort De Kock Bukittinggi, 2023)
Background: The COVID-19 pandemic is still being felt by the world and Indonesia. The impact of the pandemic has also affected the education sector. Currently learning in Indonesia is conducted face-to-face, as well as the clinical practice of Nurse Professional Education. With changes in the situation raises its own constraints and challenges. The aim of the research is to explore the experiences of students practicing the clinical practice of Nurse Professional Education during the COVID-19 pandemic. Methods: This type of research is qualitative with a phenomenological approach. Total sample of 10 participants using purposive sampling technique. Data collection was carried out by in-depth interviews and data were analyzed using content analysis. Results: The results of the study obtained five themes, namely: (1) Feelings of fear and anxiety carrying out clinical practice, (2) Efforts to reduce the risk of being infected with COVID-19 during practice, (3) Violations in the use of PPE during practice, (4) Obstacles to guidance during a pandemic, and (5) Achievement of competencies that have not been optimal related to changes in methods and areas of clinical practice. Conclusion: The results of this study provide an overview of the need for educational institutions and practice areas to develop guidance methods and methods for carrying out clinical practice for Nurse Professional Education in a pandemic situation to increase student competency achievement.Keywords: Experience, clinical practice, nurse professional education, COVID-19